Energy-efficient routing in Wireless Sensor Networks for delay sensitive applications. (27th January 2010) - Pothuri, Pavan K.; Ranganathan, Divya L.; Sarangan, Venkatesh; Radhakrishnan, Sridhar
Wireless Sensor Networks (WSNs) have enabled a plethora of new services and applications. While several routing protocols have been proposed for WSNs, these protocols tend to increase the end-to-end delay involved in data transmission. This leads to the Delay-Constrained, Energy-Efficient Routing Problem (DCEERP) in certain applications. This paper presents a methodology for solving the DCEERP using topology control in WSNs that adopt contention based channel access. The proposed solution takes in to account the access delays caused by the underlying MAC layer. Results show that the proposed framework achieves a good balance between data transfer latency and energy consumption.